United Nations participants in the Korean War the contributions of 45 member countries - Edwards, Paul M. (McFarland, 2013)
" When in 1950 the United Nations called upon its members to provide aid to South Korea, 45 nations responded. Some sent troops, some sent commodities and medical supplies, some political support but not aid. This book looks at the nations involved, what was behind their willingness to provide troops or aid, or what prevented them"--
Includes bibliographical references and index
A brief history of the Korean War -- The role of the United Nations -- Who is to fight? -- Nations providing fighting forces -- Nations that provided medical units -- Nations that provided commodities -- Silent partners -- Acceptance deferred
Keywords: United Nations / Armed Forces / History / Korean War, 1950-1953; United Nations; Vereinte Nationen; Korean War, 1950-1953; Geschichte; Koreakrieg; Beteiligung